Fabrication of 3D ordered mesoporous nickel phosphide for efficient hydrogen evolution reaction. (26th January 2023) - Zhao, Xixi; Wu, Wenzhe; Gai, Hengjun; Song, Hongbing; Xiao, Meng; Zhu, Quanhong; Liang, Jilei; Huang, Tingting
Abstract: This article successfully fabricates ordered mesoporous nickel phosphide (OM-Ni2 P) by a nanocasting method using KIT-6 as the template and nickel nitrate as the nickel precursor. The synthesized OM-Ni2 P catalyst perfectly repeats the highly symmetrical mesoporous structure of KIT-6 and exhibits a large amount of the active Ni substance Ni δ+ and the active P substance P δ− . The ordered mesoporous structure not only promotes electron transfer but also facilitates the diffusion of the reaction medium. OM-Ni2 P shows superior hydrogen evolution reaction (HER) electrocatalytic performance than the CA-Ni2 P catalyst with a disordered mesoporous structure. The OM-Ni2 P material is promising to be a substitute to Pt-based electrocatalysts for hydrolysis. Graphical abstract: Image 1 Highlights: The ordered mesoporous OM-Ni2 P catalyst was prepared by nanocasting method. OM-Ni2 P possesses more active Ni substance Ni δ+ and active P substance P δ− . The ordered mesoporous structure promotes electron transfer and facilitates reaction medium diffusion. OM-Ni2 P exhibits high HER performance of water electrolysis.